Life‐threatening gastrointestinal bleeding from splenic artery pseudoaneurysm due to gastric ulcer penetration treated by surgical hemostasis with resuscitative endovascular balloon occlusion of the aorta: A case report. Issue 3 (10th March 2022) - Nakata, Tomonori; Okishio, Yuko; Ueda, Kentaro; Nasu, Toru; Kawashima, Shuji; Kunitatsu, Kosei; Kato, Seiya
Abstract: We report the case of a patient for whom surgical hemostasis of gastrointestinal bleeding due to a splenic artery pseudoaneurysm, which developed due to gastric ulcer penetration, was achieved with resuscitative endovascular balloon occlusion of the aorta without ischemia of organs including the spleen. Abstract : Upper gastrointestinal bleeding caused by ruptured splenic artery pseudoaneurysms (SAPs) confers a significant risk. Thus, strategies involving resuscitative endovascular balloon occlusion of the aorta play a crucial role in treating ruptured SAPs.